Mitral Valve Repair in Pediatric Patients with Dilated Cardiomyopathy and Mitral Insufficiency: Single-Center Experience and Results - Mustafa Yılmaz; Başak Soran Türkcan; Ata Niyazi Ecevit; İbrahim Ece; Hazım Alper Gürsu; Atakan Atalay (Gazi Medical Journal)
Objective: Idiopathic dilated cardiomyopathy (DCM) is a serious disease causing mitral regurgitation and contraction defects of the myocardium. Through mitral valve (MV) repair surgery, the clinical status of patients can be improved. Methods: Pediatric patients with DCM and mitral insufficiency who underwent mitral repair procedures between 2019 and 2023 were retrospectively investigated. The patients’ demographic characteristics, preoperative and postoperative clinical conditions, and echocardiographic findings were compared. The techniques used in patient operations were examined. Similarly, data regarding the postoperative intensive care unit processes and mortality data of the patients were recorded. Results: Mitral repair was performed in 3 patients during the study period. The mean age of the patients was 4.66 months (±3.05) and body weight was 5.25 kg (±0.25). In the preoperative period, left ventricular ejection fraction decreased slightly in all patients [mean: 43.3% standard deviation (SD): ±2.8]. Although the preoperative and postoperative values of left ventricular end-diastolic diameter (LVEDd) and LVEDd Z-scores were above normal, respectively, they showed a decreasing trend after the operation. Although the mitral annulus diameters decreased slightly after the operation in all three patients, they remained high (mean: 17.6 mm SD: ±1.5). A significant decrease in MV insufficiency was observed in postoperative follow-ups after discharge (1st-2nd degree). Wooler annuloplasty and posterior valve pericardial patch augmentation were applied as the primary approach in all patients. The patients did not develop additional morbidities, and no mortality was observed during hospitalization. Conclusion: Successful surgical interventions to prevent mitral regurgitation in pediatric patients with DCM and mitral regurgitation, may improve the clinical status of these patients.